Estudo do efeito magnetocalórico e barocalórico de sistemas magnéticos baseados em Mn - Silva Júnior, José Almeida da (2017)
In this work we detail the magnetoelastic coupling method in which the elastic term is absorbed by the exchange term allowing it to obtain additional contributions, Sadd, to the total entropy variation, by means of the dependence of the exchange parameter (T;H; P). For this purpose, we proposed the dependence of the bulk modulus with temperature, B(T), for the linear case (L-case) and Wachtman type (W-case), thus verifying that the total entropy variation , SMaxwell, is the sum of the conventional entropy variation, Sconv, with the additional contribution, that is, SMaxwell = Sconv + Sadd. In addition, we analyzed: i) the action of hydrostatic pressure on magnetic and magnetocaloric properties for both L and W cases, where there was a reduction in transition temperature, TC, a change in nature of the magnetic transition and the increase in the intensity of the magnetocaloric e ect, Siso, keeping constant the area under the curves, with increasing pressure; (ii) the action of the magnetic eld on the barocaloric properties, where an increase in TC and a reduction of the barocaloric e ect, bar iso , could be observed, constant keeping the area under the curves, with the increase of the magnetic eld, thus verifying that the barocaloric e ect is energetically more e cient under the action of low elds than the magnetocaloric e ect; and (iii) the action of the magnetic eld and the pressure simultaneously, verifying an alternative way to potentiate the magnetocaloric e ect for a wide temperature range, which makes possible to apply the results to other systems besides MnAs and their parents. Finally, an extension of the Kubo and Ohata model, similar to Bean-Rodbell, was presented for the manganites, La1-xCaxMnO3 and La2=3(Ca1-xSrx)1=3MnO3, in the presence of magnetic eld, thus describing its magnetic, magnetocaloric, barocaloric and structural properties, by means of such magnitudes as: magnetization, variation of magnetic entropy, deformation, double exchange energy and electron conduction bandwidth eg, thus showing the connectivity between these quantities in the description of the physical properties of these compounds and showing an alternative model in the theoretical study of these manganites of Lanthanum.